Aplikasi Analytical Hierarchy Process dan Goal Programming untuk Merencanakan Pembangunan Perekonomian - Bambang Suhardi (Performa: Media Ilmiah Teknik Industri, 2002)
In order to develop the economic regional we have to consider their economic potentials and advantages obtained from its environment. Due to respect to this facts, this research proposes utilizing the analytical hierarchy process and goal programming for optimization. First, we have to develop goal programming model with objective functions and its contrains. Then we determine the weights of each criteria and relatif interest inter sub region based on analytical hierarchy process. Finally, we determine achieving function of all objective functions. With QS assistance will be obtained optimal economic sector and location of each sector.